Essential treatment and nursing for the relatively long-term survivors of paraquat intoxication - Hasegawa, Sachiyo; Suzuki, Kanae; Ohashi, Hiroko; Urata, Kazuyo; Kozawa, Taeko; Niwa, Kyoko; Mine, Fumiko (Journal of Japanese Society for Dialysis Therapy, 1986)
A 30-year-old woman was admitted to the hospital because of paraquat ingestion. She was in her usual state of good health until an attempt at suicide. Although she complained of a sore throat and general irritability only, her husband prompted her to visit the hospital just after she took 10ml of concentrated paraquat solution. Immediately after forced diuresis with continuous administration of a large volume of electrolyte solution, recurrent intestinal lavage and direct hemoperfusion were performed prospectively because it was supposed that liver, kidney and lung involvement would develop subsequently. Several days after admission, jaundice was noticed, and urine volume was abruptly reduced. Hemodialysis was successfully continued for one week for the treatment of acute renal failure. Liver function impairment and renal insufficiency were ameliorated during the one-week course, but unfortunately on the fifth day, a cloudy opaque shadow appeared on the chest X-ray film, suggesting that one of the most important complications, lung fibrosis, had begun. Paraquat toxicity is considered to be elicited by generation of superoxide radicals and lipid peroxides in the paraquat oxidation/reduction cycle, and lung fibrosis could be accelerated by hyperbaric O2 air. Therefore, FiO2 was maintained carefully as low as possible, keeping the patient's PaO2 at least above 50 Torr. She died on the 21st day because of fatal airway bleeding. Hemodialysis may be the most important procedure for treatment of renal insufficiency, but it cannot play an important role in eliminating paraquat from tissues because clearance of paraquat is very low, the paraquat concentration of tissues is higher (×6 for lung) than that of serum, and even a very low serum paraquat concentration (below 0.5ppm) is still lethal. As described above, paraquat intoxication would be more severe and develop earlier when the patient is exposed to hyperbaric O2. Hemodialysis personnel must, therefore, understand the pathodynamics of paraquat intoxication and avoid careless use of O2.